2013
DOI: 10.1523/jneurosci.1037-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Stable, Robust, and Adaptive Development of Orientation Maps in the Primary Visual Cortex

Abstract: Development of orientation maps in ferret and cat primary visual cortex (V1) has been shown to be stable, in that the earliest measurable maps are similar in form to the eventual adult map, robust, in that similar maps develop in both dark rearing and in a variety of normal visual environments, and yet adaptive, in that the final map pattern reflects the statistics of the specific visual environment. How can these three properties be reconciled? Using mechanistic models of the development of neural connectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
98
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(104 citation statements)
references
References 88 publications
5
98
1
Order By: Relevance
“…Conversely, self-organizing models with shallow architectures have long been known to produce topographical and topological maps under a variety of activity-dependent learning rules [87][88][89][90][91][92]. One such model [90] simulates the emergence of separate areas for letters and digits by spontaneous symmetry-breaking, but fails to explain the systematic location of these cortical territories.…”
Section: Box 2 Deep Learning Network and Symbol Form Areasmentioning
confidence: 99%
“…Conversely, self-organizing models with shallow architectures have long been known to produce topographical and topological maps under a variety of activity-dependent learning rules [87][88][89][90][91][92]. One such model [90] simulates the emergence of separate areas for letters and digits by spontaneous symmetry-breaking, but fails to explain the systematic location of these cortical territories.…”
Section: Box 2 Deep Learning Network and Symbol Form Areasmentioning
confidence: 99%
“…Later studies demonstrated that cortical orientation maps are organized in a mosaic consisting of iso-orientation domains arranged radially around pinwheel centres, where orientation preference changes rapidly along the circular locus234. Although many models have been proposed to explain how the beautiful geometrical properties of the pinwheel pattern could develop5678 and why they are remarkably similar across many species, the visual cortices of many mammals including rodents, squirrels and lagomorphs do not have orientation maps91011. Therefore, it remains a mystery whether topographically mapping stimulus orientation is an epi-phenomenon or has significant functional implications121314.…”
mentioning
confidence: 99%
“…This theoretical formulation has demonstrated the possibility of LTP and homeostasis in the formation of orientation, ocular dominance, and direction preferences in the primary visual cortex (Bednar and Miikkulainen 2006;Stevens et al 2013), the development of whisker direction maps in rat barrel cortex (Wilson et al 2010), and the formation of selectivity to angles in visual area V2 (Plebe 2007(Plebe , 2012.…”
Section: Intra-map Plasticitymentioning
confidence: 98%